Knowledge : a very short introduction - Nagel, Jennifer (New York : Oxford University Press, Oxford University Press, 2014)
What is knowledge? How does it differ from mere belief? Can we know that the outer world is real and not a dream? Epistemology is the branch of philosophy devoted to answering questions like these. This Very Short Introduction explores classical and contemporary epistemology, covering topics from ancient relativism and scepticism to the trustworthiness on internet sources. Using intuitive examples and ideas from linguistics and psychology, as well as philosophy, Jennifer Nagel explains what we now know about knowledge.
1. Introduction -- 2. Scepticism -- 3. Rationalism and empiricism -- 4. The analysis of knowledge -- 5. Internalism and externalism -- 6. Testimony -- 7. Shifting standards? -- 8. Knowing about knowing.
Includes bibliographical references and index.
Keywords: Knowledge, Theory of; Knowledge; Sciences cognitives; Acquisition de connaissances; Philosophie; Knowledge, Theory of